GROWTH AND BIOCHEMICAL COMPOSITION OP POSTEMBRYONIC CARP TREATED WITH YEAST - Das, B C (Indian Journal of Fisheries, 2011)
BREWERS’ yeast, an ascomycetous fungus (Sacchawniyces cerevisiae), promotes the growth of postembryonic Indian carp [species La^eo rohita (Ham.), family Cyprinidae] (Das, 1960 Z>; 1964; 1965 b). The dry weight of carp treated daily during the first two weeks of postembryonic Ufe is double or triple that of untreated control carp. The effect of yeast is dependent on dosage, within the range of 0-05 to 0-22 g per litre of water containing 50 to 70 young carp. Higher dosages, within the range of 0;22 to 0-44 g, do not yield weight increase beyond those obtained at 0-22 g (Das, 1965 b). Having established the beneficial effect of yeast on growth of postembryonic carp^ the next problem is to determine how or in what way yeast accomplishes its effect. For this purpose, an experimental study of the total protein, nonprotein nitrogen, acid phosphatase and alkaline phosphatase of postembryonic carp has been carried out. MATERIALS AND METHODS One-day-old Labeo rohita were